2017
DOI: 10.1136/bmjopen-2016-015500
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and prioritising systematic review topics with public health stakeholders: A protocol for a modified Delphi study in Switzerland to inform future research agendas

Abstract: IntroductionThe Cochrane Collaboration aims to produce relevant and top priority evidence that responds to existing evidence gaps. Hence, research priority setting (RPS) is important to identify which potential research gaps are deemed most important. Moreover, RPS supports future health research to conform both health and health evidence needs. However, studies that are prioritising systematic review topics in public health are surprisingly rare. Therefore, to inform the research agenda of Cochrane Public Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
(28 reference statements)
0
12
0
1
Order By: Relevance
“…As with all research, priority setting is important for systematic review studies to identify the most important research gaps and health evidence needs. 17 Moving forward with future iKT projects, we will more carefully consider the prioritization issue and use existing processes (eg, The Cochrane Collaboration Review Groups frameworks, approaches, or methods for prioritization in systematic reviews), which may help to guide preliminary KU conversations and narrow the focus. 18 In this study, we reached consensus on study objectives by gathering individual feedback from KUs, compiled each idea into a project large in scope, and then received agreement from each KU individually.…”
Section: Discussionmentioning
confidence: 99%
“…As with all research, priority setting is important for systematic review studies to identify the most important research gaps and health evidence needs. 17 Moving forward with future iKT projects, we will more carefully consider the prioritization issue and use existing processes (eg, The Cochrane Collaboration Review Groups frameworks, approaches, or methods for prioritization in systematic reviews), which may help to guide preliminary KU conversations and narrow the focus. 18 In this study, we reached consensus on study objectives by gathering individual feedback from KUs, compiled each idea into a project large in scope, and then received agreement from each KU individually.…”
Section: Discussionmentioning
confidence: 99%
“…Prioritisation projects relying solely on respondents to write-in their proposed topics have been conducted, [7] or are currently in progress, [14] however, this approach has previously been found to yield a very large number of unanswerable questions. For example, a similar exercise by the Cochrane Tobacco Addiction Group found that of the 258 questions suggested by the respondents, 183 (or 71%) were unanswerable.…”
Section: Discussionmentioning
confidence: 99%
“…18 The Delphi process is commonly modified and, on the basis of available evidence, the researchers selected a modified two-round Delphi study as most appropriate for this study. [19][20][21][22]…”
Section: Methodsmentioning
confidence: 99%